Ginsenoside Rg3 attenuated omethoate-induced lung injury in rats. (June 2016) - Wang, J; Yu, XF; Zhao, JJ; Shi, SM; Fu, L; Sui, DY
Organophosphorus exposure affects different organs such as the lung, gastrointestinal tract, liver, and brain. The present experiment aimed to evaluate the effect of ginsenoside Rg3 on lung injury induced by acute omethoate poisoning. Rats were administered with omethoate subcutaneously at a single dose of 60 mg/kg, followed by ginsenoside Rg3 (5, 10, or 20 mg/kg) treatment. Histopathological examination of the lung was performed at 24 h after the omethoate exposure. The antioxidative parameters in the lung were also assayed. Moreover, the activities of acetylcholinesterase, myeloperoxidase, and the content of tumor necrosis factor α (TNF-α) in the lung were determined. The results showed that ginsenoside Rg3 attenuated omethoate-induced lung injury. Ginsenoside Rg3 increased the level of glutathione in the lung ( p < 0.05 or p < 0.01). The altered activities of superoxide dismutase and catalase in the lung were also ameliorated by ginsenoside Rg3 treatment ( p < 0.05 or p < 0.01). Ginsenoside Rg3 caused significant reductions in the contents of malondialdehyde, TNF-α, and the activity of myeloperoxidase ( p < 0.05 or p < 0.01). The present study demonstrated that ginsenoside Rg3 had a protective effect against omethoate-induced lung injury in rats, and the mechanisms were related to its antioxidant potential and anti-inflammatory effect.